SYSTEMATIC LITERATURE REVIEW : PENERAPAN ARTIFICIAL INTELLIGENCE DAN PEMANFAATAN PENGUNGKAPAN LAPORAN KEUANGAN DALAM MEMPREDIKSI HARGA SAHAM - Andila Fani Diah Eka Wardani; Dwi Cahyo Utomo (Diponegoro Journal of Accounting, 2026)
This study aims to identity the roles and patterns emerging g from previously published research that has had a significant impact on stock price prediction using artificial intelligence. The focus of this study is directed toward literature that examines the contribution of artificial intelligence to stock price forecasting, as well as mapping the extent to which artificial intelligence utilizes financial report disclosures as an information source in the prediction process. The Systematic Literature Review (SLR) method is employed to analyze various articles published in academic journals within the ScienceDirect database. The selected articles consist of publications from 2015 to 2025 that were filtered using specific keywords. This study reviews articles that apply artificial intelligence, machine learning, or deep learning in stock price prediction. In addition, ChatPDF and ChatGPT are used as supporting tools during the literature review process, and VOSviewer is utilized for bibliometric analysis. The results reveal a variety of roles and patterns in the use of artificial intelligence for stock price prediction based on different input approaches, including technical analysis, fundamental analysis, sentiment analysis, and other findings. The outcomes of this study are expected to provide meaningful benefits and significant contributions by enhancing knowledge and enriching the literature related to the application of artificial intelligence in stock market prediction.